NON-FINANCIAL INFORMATION AND INTEGRATED REPORTING IN THE HOSPITALITY INDUSTRY: CASE STUDY OF CROATIA - Milena Peršić; Lahorka Halmi (Copernican Journal of Finance & Accounting, 2018)
Subsequent to the Directive 2014/95/EU (EUDNFI) and Croatian Accounting Act (CAA), available non-financial information disclosed by Croatian hospitality companies in non-financial (sustainability) reports were analysed for their breadth and quality using the content analysis method The results of preliminary research of hospitality industry were used in order to explore the specifics of non-financial reporting in the hospitality industry, using case study method. Results reveal the highest scores among the quality principles is timeliness, among areas are environment, labour practice, and community/society, and an overall score to be 7.67 (out of 30). The lowest scores of quality principles were reliability and comparability, whereas areas were product and human rights. The results point to a need for establishing a framework for disclosing non-financial information in reports to make them useful to internal and external users. Therefore, relevant opinions of experts, bodies and associations, such as CSR Europe, International Integrated Reporting Council, GRI’s Corporate Leadership Group, will be considered in creating a model, with a particular emphasis on the globally accepted sustainability accounting standards.